Association of Serum Ceruloplasmin Level with Obesity: Some Components of Metabolic Syndrome and High-Sensitive C-Reactive Protein in Iran - Seyyed Morteza Safavi; Rahele Ziaei; Mohammad Reza Maracy (Journal of Obesity)
Background. One of the mechanisms that has been suggested for obesity related metabolic disturbances is obesity-induced inflammation. Pro-inflammatory cytokines generated in adipose tissue can increase hepatic synthesis of inflammation-sensitive plasma proteins (ISPs) including ceruloplasmin (Cp). In this study we aimed to investigate the relation between serum Cp level and obesity. Methods. 61 persons with body mass index (BMI) ≥ 25 kg/m2 (case group) and 61 persons with BMI < 25 kg/m2 (control group) were included in this study with a case-control design. Serum Cp levels, triglyceride level, fating blood glucose, total cholesterol, LDL-cholesterol, HDL-cholesterol and hsCRP were measured in both groups. Results. We did not observe any significant association between serum Cp level and BMI in all subjects [OR: 1.02 (CI, 0.967 to 1.07)] and in case (β=0.012, P=0.86) and control groups (β=0.49, P=0.07) separately. However, in control group, this positive association was marginally significant. We found a positive correlation between serum Cp level and serum triglyceride level. Conclusion. Serum Cp level was not related to obesity in this group of subjects. None of the baseline variables could predict obesity in this group of subjects, including serum Cp level, FBS, total cholesterol, LDL and HDL- cholesterols and hsCRP.